Cerebral angiographic features of central retinal artery occlusion patients treated with intra-arterial thrombolysis. (6th September 2021) - Kim, Jongshin; Jung, Seunguk; Park, Kyu Hyung; Woo, Se Joon; Jung, Cheolkyu
Abstract : Background: Central retinal artery occlusion (CRAO) is an ischemic stroke of the eye. The atherosclerotic lesions in the intracranial segment of the carotid artery (CA) and the ophthalmic artery (OphA) are not well defined. We aimed to investigate the cerebral angiographic features of CRAO patients and assess the relationship between the angiographic features and outcomes after intra-arterial thrombolysis (IAT). Methods: We included 101 acute non-arteritic CRAO patients treated with IAT. We analyzed the detailed angiographic features of the OphA and ipsilateral CA, visual acuity, fundus photography, and fluorescein angiography. Results: Of the 101 patients, 38 patients (37.6%) had steno-occlusive lesions in the OphA, and 62 patients (61.4%) had atherosclerotic lesions in the ipsilateral CA. The patients with a higher degree of stenosis in the OphA showed a higher degree of stenosis (P=0.049) and a more severe morphology of plaque (P=0.000) in the ipsilateral CA. Additionally, although the visual outcome was not associated with these angiographic features, the lower degree of stenosis and less severe morphology of plaque in the ipsilateral CA resulted in a significant improvement in early reperfusion rate (P=0.018 and P=0.014, respectively) and arm-to-retina circulation (P=0.016 and P=0.002, respectively) of the eye after IAT. Conclusions: There was a significant correlation in the severity of steno-occlusive lesions between the OphA and the ipsilateral CA in patients with CRAO. The patients with less severe angiographic features in the CA showed a more improved retinal reperfusion after IAT. The angiographic findings in the CA may serve as a predictive marker for the vessel integrity of the OphA and recanalization outcome after IAT.